2008
DOI: 10.1098/rspb.2008.0994
|View full text |Cite
|
Sign up to set email alerts
|

Human-related processes drive the richness of exotic birds in Europe

Abstract: Both human-related and natural factors can affect the establishment and distribution of exotic species. Understanding the relative role of the different factors has important scientific and applied implications. Here, we examined the relative effect of human-related and natural factors in determining the richness of exotic bird species established across Europe. Using hierarchical partitioning, which controls for covariation among factors, we show that the most important factor is the human-related community-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
91
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 36 publications
(74 reference statements)
4
91
1
Order By: Relevance
“…Recent studies have demonstrated that on broad spatial scales, the impact of human activities overwhelms the influence of climate and geography on species invasions (3,4,24). The results of the current analysis extend our understanding of the temporal dimension of this relationship.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Recent studies have demonstrated that on broad spatial scales, the impact of human activities overwhelms the influence of climate and geography on species invasions (3,4,24). The results of the current analysis extend our understanding of the temporal dimension of this relationship.…”
Section: Discussionsupporting
confidence: 65%
“…sequent establishment in the wild (14,25). Such a delay probably results from the time necessary to exceed critical thresholds of available propagules (8) that will, in turn, depend on factors like the numbers of introduction events and of individuals introduced (7,8,24,26), the type of introduction pathway (9,27), the match between an alien-species' habitat requirements and the conditions in the new territory (9), the length of generation times (14,28,29), or the time necessary for genetic adaptations to the new environments (8). This multitude of potentially interacting factors renders any generalization about the magnitude of such a delay difficult and probably also explains why the relative strengths of historical and contemporary models are not consistent among taxonomic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Wonham & Pachepsky (2006) considered the influence of 'introduction rate' on temporal trends in the rate that invasive species accumulate at a site, where introduction rate is the number of species introduced in any given time period. Chiron et al (2009) concluded that 'community-level propagule pressure', defined as the number of exotic species introduced, was a major driver of the observed variation in the number of established species across Europe. In these contexts, propagule pressure, introduction rate and community-level propagule pressure are all synonyms of colonization pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Propagule pressure is therefore closely linked with human activities and, indeed, there is increasing evidence that macroeconomic and macroecological variables need to be integrated in the same model if we are to understand the drivers of biological invasions more precisely (1,21). To date, such studies are relatively few and most focus on one or a few taxonomic groups (24,25). A study aimed at revealing general determinants of biological invasions common to a wide range of taxonomic groups that would weigh the relative importance of ecological factors and human factors will be pivotal for policymakers and future management.…”
mentioning
confidence: 99%